Processo de produção jornalístico: a edição no fotojornalismo pós convergência das mídias - Fávaro, Armando (2013)
In this study we aim to analyze the role of image's edition in the process of creating the first page of a newspaper in its various platforms, as well as on the homepage of its news portal, in order to establish the relevance of photography in the constitution of the communication process. Poorly explored phenomenogically - since the main focus of the research addresses the production and analysis of images - photographic editing is crucial at the arrangement of the syntagmatic elements that constitute those capital pages. By employing the use of the methodology built on the foundations of genetic criticism of Peirce's semiotic approach, this paper will focus on the study of the first pages of some O Estado de S. Paulo newspaper s edition in its several platforms, including homepages of its news site. In order to investigate the paradigms that rule the choice of journalistic images, we will analyze the pages of specific editions of this periodical through unpublished's documents (such as rafes, scribbles, layouts, drawings, images options and other instruments) which were used to compare it with its direct competitors in the country and from major newspapers from abroad (in its various platforms), so as to understand how the images began to have utmost importance in the preparation of these pages, once the photojournalism acquired by extending its statements beyond the photograph a decisive role in this production system. The advances in the production process of the media, with the introduction of electronic technologies of imaging and news, contributed to a new level in the production, transmission and editing of images, which determined an evolutionary parameter on the contemporary photojournalism, that gives rise to a new specificity: the production and editing of moving images.The convergence of the media and its tools to structure and enable the newspaper broadcasting in different platforms and promote greater interactivity with the public, caused a change in the profile of the professionals involved in the journalistic environment, consolidating the multimedia photojournalist as a major component in this process.Thus, the advancement of this study consolidates the purpose to develop a theoretical reflection on the photo editing within the new productive grammar of journalistic creation process